Fundamentals of mental health nursing - Clarke, Victoria; Walsh, Andrew (New York : Oxford University Press, 2009)
This is a case-based, service user-centred textbook for mental health nursing students to use throughout their pre-registration studies. The essential theory required for nursing care is explored alongside real service users' views and fictional cases
1. On becoming a student mental health nurse -- 2. Fundamental skills of mental health nursing -- 3. Mental health law -- 4. Community mental health nursing care of a person with complex needs -- 5. The nursing care of an adult in crisis with mental health problems -- 6. Mental health nursing in a rehabilitation and recovery context -- 7. The nursing care of older people with mental health problems -- 8. Mental health nursing in the community -- 9. Additional skills for complex cases in mental health nursing -- 10. On becoming a qualified mental health nurse
Includes bibliographical references and index
Keywords: Psychiatric nursing; Psychiatric nursing -- Case studies; Psychiatric Nursing -- methods; Mental Disorders -- nursing